P-BN26 The effect of cholecystectomy on unplanned admissions following endoscopic sphincterotomy and bile duct stone removal. (16th December 2021) - Toogood, Kate; Pike, Thomas; Coe, Peter; Everett, Simon; Huggett, Matthew; Paranandi, Bharat; Bassi, Vinod; Toogood, Giles; Smith, Andrew
Abstract: Background: Choledocholithiasis is common, with patients usually treated with ERCP and subsequent cholecystectomy to remove the presumed source of common bile duct (CBD) stones. However, previous investigations into the management of patients following ERCP have focussed on recurrent CBD stones, negating the risks of cholecystectomy. Methods: Patients undergoing ERCP and CBD clearance for choledocholithiasis at St James's University Hospital January 2015 - December 2018 were included. Patients were divided into those who received cholecystectomy and those managed non-operatively. Readmissions, operative morbidity, mortality and treatment costs were investigated. Results: 844 patients received ERCP and CBD clearance with 3.9 years follow up. 209 patients underwent cholecystectomy with 15% requiring complex surgery. 373 patients were non-operatively managed. Unplanned readmissions occurred in 15% following ERCP, mostly within two years. There was no difference in readmissions between the two groups. Accounting for the entire patient pathway, non-operative management was less expensive. Conclusions: The majority of patients do not require readmission following ERCP for CBD stones and cholecystectomy did not reduce the risk of readmission. Few patients have recurrent CBD stones, but difficult biliary surgery is frequently required. Routine cholecystectomy following ERCP needs to be re-evaluated and a more stratified approach to future risk developed.